TEACHING VOCABULARY TO ELEMENTARY LEVEL STUDENTS LEARNING RUSSIAN AS A FOREIGN LANGUAGE: TOPIC «MY FAMILY AND I» (Филологический класс, 2017)
The article describes a lesson «My Family and I» for elementary level students learning Russian as a foreign language. This topic is the first in the academic subject Russian Vocabulary. The article sums up the experience of teaching this subject to Chinese students learning Russian at the Ural State Pedagogical University. The content and the aims of the lesson «My Family and I», as well as the subject Russian Vocabulary, are based on the communicative approach to teaching Russian as a foreign language. The subject is not supposed to train for certificate exams in Russian but it is taught meeting the requirements to the scope of vocabulary and prescribed topics for the elementary level.